Optimisation of rotational moulding of polyethylene by predicting antioxidant consumption - Cramez, M. C. (2002)
Rotational moulding is used to manufacture hollow plastic products. The process offers many advantages to the designer, but it is hampered by a strong dependence on trial and error methods to achieve good part quality at economic production rates. During rotational moulding, the polymer is subjected to relatively high temperatures for long periods of time in the presence of air. This can lead to degradation of the polymer at the inner free surface of the moulded article, with consequent deterioration of the mechanical properties of the part. The processing conditions that lead to degradation vary with factors that affect the heating rate, such as the type of mould used. In this work a method is proposed to predict the onset of degradation, on the basis that this occurs when the concentration of anti-antioxidant in the polymer reaches zero. Good agreement between the experimental and predicted optimum processing temperature was obtained for two grades of polyethylene stabilised with two different antioxidant systems. Using the method described, it is now possible to identify the best rotational moulding conditions for a particular polymer so that more efficient cost-effective parts can be produced.